Christine - Carpenter, John.; Alexandra, Paul.; Christine Belford; Harry Dean Stanton; John Stockwell; Robert Prosky; Roberts Blossom; Keith Gordon (USA Columbia Pictures Corporation, 1983)
Highschool geek Arnie Cunningham falls in love with ""Christine"", a bright red 1958 Plymouth Fury which has seen much better days. Setting himself the task of restoring the car to its original condition, his friends notice that the car is not the only thing that is changing. Arnie seems to spend more and more time with his car. He's also developed a sort of cocky arrogance which does not seem like the real Arnie at all.
A nerdish boy buys a strange car with a evil mind of its own and his nature starts to change to reflect it.
Stephen King
Languages: English, German, French Subtitles: English, Turkish, German, French, Spanish, Italian, Russian, Czech, Dutch, Serbo-Croatian, Portuguese
Keywords: Fantasy; Horror; Thriller; Drama